Respons Pertumbuhan Dan Hasil Tanaman Melon (Cucumis melo L.) Terhadap Macam Media Tanam Dan Pestisida Organik - Afriyani, Risma Ayu; Carsidi, Didi; Asad, Faisal Al; Sumarna, Pandu; Mahmud, Yudhi (Jurnal Agro Wiralodra, 2024)
Melon production in Indonesia is currently unable to meet the needs of public consumption, so melon production must continue to be increased. This study aims to determine the dosage of organic pesticides on certain growing media that can produce the best growth and yield of melon plants. The research was conducted in Karanganyar Village, Indramayu District, Indramayu Regency. The study used an experimental method with a Split-Plot Design 2 x 3 repeated 4 times. The main plot is the growing media with 2 levels; M0 = Land, M1 = Soil + Bokashi. Subplots were a combination of organic pesticides Bio T10 and Bio P60 with 3 levels; B0 = Without Dosage of Bio T10 and Bio P60, B1 = Dosage of 2 ml of Bio T10 and 1 ml of Bio P60, B2 = Dosage of 3 ml of Bio T10 and 1.5 ml of Bio P60. The results showed that the growing media significantly affected plant height, number of leaves, stem diameter, and leaf area. The best type of growing media is shown by soil treatment and bokashi. The dose of organic pesticides significantly affects plant height and number of fruit seeds. The best dose of organic pesticides was shown by organic pesticide treatment with a combination dose of 3 ml of Bio T10 and 1.5 ml of Bio P60.